Getting Lost In The “Realm Of Possibility”: Common Phrases Used To Communicate Rare Events Have Substantially Different Effects On Decision-Making (Journal of International Crisis and Risk Communication Research, 2023)
Communicating probabilities is challenging. Numbers are precise, but poorly understood by the public. Verbal phrases (“it is unlikely”) can be misinterpreted. The current study used a binary decision task (total n = 3207) to compare how varieties of verbal and numerical phrases impact decision-making. We identified “realm of possibility” phrases from real-world risk communications. These produced substantially higher risk perceptions compared to other formats. Verbally-formatted phrases increased risk perceptions compared to numerically-formatted ones. Contrary to previous findings, the “1-in-X” format did not uniformly increase risk perceptions compared to when percentages were used. When using the “1-in-X” format, risk perceptions decreased monotonically with the increased probability of negative decision outcomes. With percentages, risk perceptions instead showed a curvilinear (and contradictory) trend.